Phonological and Vocabulary Acquisition in Early Childhood: An Ethnography of Communication in a River-Based Multidialect Community - Novi Suma Setyawati; Armin Fani; Novi Nurdian (Papanda Publisher, 2026)
This study examines phonological and vocabulary acquisition in early childhood within a multidialectal river-based community in South Kalimantan, Indonesia, where Dayak Bakumpai and Banjar dialects are used concurrently. Employing a qualitative ethnography of communication approach, the research was conducted over six months in Kuripan District, involving 20 children aged 4–6 years, along with 10 parents and 5 teachers selected through purposive sampling. Data were collected through participant observation, in-depth interviews, and audio-visual documentation across home, school, and community contexts. Thematic analysis revealed that children demonstrated phonological flexibility, adjusting pronunciation and prosody according to interlocutor and context, while developing balanced productive vocabularies that expanded substantially across age groups (120/110 words at age four to 280/270 words at age six for Bakumpai/Banjar respectively). Sustained exposure to both dialects across multiple social domains supported concurrent acquisition of dual phonological systems and context-sensitive lexical deployment. Children exhibited early metalinguistic awareness, explicitly recognizing dialectal differences. The findings demonstrate that multidialectal acquisition constitutes a distinct developmental phenomenon requiring theoretical frameworks extending beyond monolingual-bilingual dichotomies. This study contributes to language acquisition theory by highlighting dialectal variation as a meaningful developmental condition and informs culturally responsive language education curricula honoring Indonesia's linguistic diversity.